User Experience Analysis on the KMOB Depok Application Using the System Usability Scale Method - Putra, Erich Eryana (SAN Scientific, 2024)
To improve services to the community, Depok City has developed technology by launching KMOB, this Android-based application has met the needs of the activities of the people of West Java, especially in the centralized city of Depok. The purpose of this study is to measure the level of user experience of the KMOB application and to produce recommendations for improvements to the KMOB application based on the results of the analysis using the system usability scale (SUS) method. The method used in this research is system usability scale (SUS), the data collection used is interviews, and the distribution of SUS questionnaires to 30 KMOB application users, which are sent via google form. The results showed that the KMOB application almost on the entire assessment scale had a good (positive) evaluation, namely on the attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty assessment scale. KMOB application for Depok City was categorized as not meeting usability standards. Based on the usability evaluation, the SUS score is 44.5 with a not adjective rating including the